Manufacturing citizenship : education and nationalism in Europe, South Asia and China - Bénéï, Véronique (Routledge research in education, 2005)
Citizen-making processes in European and Asian countries are compared in this interdisciplinary text which adopts an original approach by focusing upon the concept of citizenship as an effect of the educational enterprise.